Air movement and temperature regime in large stacked apple bins during the initial phases of cold storage - Tuany Gabriela Hoffmann; Poonam Bidgar; Jincheng Yu; Daniel Alexandre Neuwald; Reiner Jedermann; Manfred Linke; Pramod Mahajan (Biosystems Engineering, 2026)

Dew point undershoot mechanisms driving surface condensation in commercial apple cold storage - Reiner Jedermann; Tuany Gabriela Hoffmann; Daniel Alexandre Neuwald; Felix Büchele; Pramod Vasantrao Mahajan (Postharvest Biology and Technology, 2026)

Anaerobic compensation point can effectively extend ‘Palmer’ mango shelf-life in CA storage - Luana Ferreira dos Santos; Tassiane Alves de Souza; João Claudio Vilvert; Jasciane da Silva Alves; Bruna Parente de Carvalho Pires; Luciano Sobral Fraga Junior; Daniel Alexandre Neuwald; Sergio Tonetto de Freitas (Postharvest Biology and Technology, 2026)

Quality of ‘Xenia’ pear under controlled atmosphere storage and 1-methylcyclopropene application - Adriana Lugaresi; Aishwarya Padrudkar; Adriano Arriel Saquet; Felix Büchele; Cristiano André Steffens; Kartik Khera; Daiane Quadros de Oliveira Neuwald; Jefferson G. Acunha; Lilian Osmari Uhlmann; Fabio Rodrigo Thewes; Adem Dogan; Michael Helmut Hagemann; et al. (Postharvest Biology and Technology, 2025)

1-Butanol applied to ‘Maxi Gala’ apples during postharvest shelf life and after dynamic controlled atmosphere: Effects on metabolism and quality - Barbara Cecconi Deon; Fernanda de Candido de Oliveira; Francis Júnior Soldateli; Carine Borges Batista; Manoela Meira Balzan; Aline de Cássia Machado; Auri Brackmann; Vanderlei Both; Daniel Alexandre Neuwald; Fabio Rodrigo Thewes; Roger Wagner (Postharvest Biology and Technology, 2025)

Challenges and future perspectives in postharvest cold storage: technological review on sustainable and efficient cold storage of fresh produce - Tuany Gabriela Hoffmann; Carolina Krebs de Souza; Akshay D. Sonawane; Ulrike Praeger; Felix Büchele; Daniel Alexandre Neuwald; Reiner Jedermann; Manfred Linke; Barbara Sturm; Pramod V. Mahajan (Food Research International, 2025)

Humidity Control and Its Implications in the Storage of Apples and Pears: A Review - Robert K. Prange; A. Harrison Wright; Barbara J. Daniels-Lake; Daniel Alexandre Neuwald; Dirk Köpcke; Luiz Carlos Argenta (Applied Fruit Science, 2025)
At harvest, the water content of apples and pears is at its maximum, about 83–85% by mass. The rate of fruit water loss after harvest is a function of three factors: the fruit surface area, the epidermis water vapour permeance, and the difference in internal and external fruit water vapour pressure. However, the water vapour pressure difference is the only factor that can be controlled during storage, i.e. by altering the storage humidity. Curiously, most publications on apple and pear storage do not discuss storage humidity even though the postharvest quality of both depends largely upon it. Apples and pears can experience up to ~ 2% mass loss without loss of commercial value, but further mass loss creates visible shrivelling, and may also increase bitter pit, depending on the cultivar. The prevailing commercial advice has been to minimise mass loss by maximising the relative humidity at the chosen storage temperature. However, this advice should be re-evaluated, and humidity management protocols revised, from minimising mass loss to optimising mass loss. Growing evidence indicates that storage humidity affects the postharvest performance of apples and pears. A review of the literature over the last 100 years shows that some mass loss, achieved by lowering storage atmosphere humidity, can improve apple and pear quality by reducing non-bitter pit disorders, bruising, respiration, ethylene production and decay, especially if the mass loss occurs at the beginning of storage. The effects of mass loss on calcium-related disorders suggest that mass loss may affect postharvest calcium redistribution in the fruit. The fruit mass loss for refrigerated air and controlled atmosphere rooms can be estimated by collecting the defrost water from the refrigeration cooling coils and expressing this as a percentage of the initial total mass of fruit in the room. A ‘2-in-2’ guideline (up to 2% mass loss in the first 2 months) is proposed, but further research is needed to refine this guidance, especially for cultivars that may benefit from greater mass loss without increasing shrivelling or bitter pit.

Static and dynamic controlled atmosphere storage and 1-methylcyclopropene treatment of ‘Cripps Pink’ apples: Linking sensory perception, volatile compounds, and quality - Fernanda de Candido de Oliveira; Manoela Meira Balzan; Barbara Cecconi Deon; Madison Willy Cordeiro; Carine Borges Batista; Francis Júnior Soldateli; Lucas Mallmann Wendt; Fabio Rodrigo Thewes; Vanderlei Both; Auri Brackmann; Daniel Alexandre Neuwald; Roger Wagner (Food Research International, 2025)

Yellowing and overall quality of ‘Legacy’ broccoli: 1-butanol vapor treatment as an alternative to 1-MCP during storage at room temperature - Fabio Rodrigo Thewes; Mateus Gaiardo dos Santos; Bruna Regina Carvalho Pinto; Guilherme Zanon Peripolli; Luise Victoria Agnes; Kaliandra Zottele Nunes; Lilian Osmari Uhlmann; Daniel Alexandre Neuwald; Auri Brackman; Roger Wagner; Vanderlei Both (Journal of Stored Products Research, 2025)

Heat transfer in large bins during the apples cool-down process - Tuany Gabriela Hoffmann; Manfred Linke; Ulrike Praeger; Akshay D. Sonawane; Felix Büchele; Daniel Alexandre Neuwald; Reiner Jedermann; Barbara Sturm; Pramod V. Mahajan (International Journal of Refrigeration, 2025)

Influence of pre-harvest calcium application on the concentration and distribution of ascorbic acid and mineral content in apple cultivars at harvest and during storage - Rachael Maree Wood; Sergio Tonetto de Freitas; Luiz Carlos Argenta; Daniel Alexandre Neuwald (Postharvest Biology and Technology, 2024)

Superficial scald development in ‘Granny Smith’ and ‘Nicoter’ apples: The role of key volatile compounds when fruit are stored under dynamic controlled atmosphere - Jossiê Zamperetti Donadel; Fabio Rodrigo Thewes; Luana Ferreira dos Santos; Erani Eliseu Schultz; Magno Roberto Pasquetti Berghetti; Vagner Ludwig; Juliana Mesadri; Bruna Klein; Flavio Roberto Thewes; Suele Fernanda Prediger Schmidt; Vanderlei Both; Auri Brackmann; et al. (Food Research International, 2023)

Interaction between dynamic controlled atmosphere (DCA-CD), 1-methylcyclopropene and elevated temperatures in the long-term storage of organic ‘Santana’ apples - Felix Büchele; Kartik Khera; Roger Wagner; Fabio Rodrigo Thewes; Daniel Alexandre Neuwald (Postharvest Biology and Technology, 2023)

Factors affecting development of disorders expressed after storage of ‘Gala’ apple fruit - Luiz Carlos Argenta; Rachael Maree Wood; James P. Mattheis; Fabio Rodrigo Thewes; Cristiano Nunes Nesi; Daniel Alexandre Neuwald (Postharvest Biology and Technology, 2023)